KOMPETISI ANTARA TANAMAN SORGUM DENGAN ROTTBOELLIA - Danner Sagala; Leo Mualim; Didi Darmadi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2011)
This research was aimed to study the competitiveness of shorgum and Rottboellia exaltata L.f.. The experiment was done at glass house, experimental station of SEAMEO-BIOTROP, Bogor on 3 Oktober – 17 November 2009. The main plant was Sorghum and the weed was Rottboellia exaltata L.f.. the result showed that the sorghum was more competitive than Rottboellia exaltata L.f..